Kelayakan dan Strategi Pengembangan Sapi Potong untuk Pengentasan Kemiskinan di Aceh - Nuhfil Hanani; Jamilah - (Jurnal Aplikasi Manajemen, 2011)
Potential development of beef cattle for Aceh region sufficient large, because supported by market potential enough milt, in other one are development region of beef cattle who enough potential. Because of that suitable and development strategy of beef cattle as superior commodity must be examine who purposed for raise poverty in Aceh.This research as examined of suitable with analyzed approach of project evaluation with entered suitable substance for purposed raise poverty. Infiltration of strategy use SWOT analyzed who completed with step development of agribusiness. The based of business scale, only at 5 beef scale who suitable developed because personal income at poverty line, whereas development of 2 beef scale only suitable if be stall and beef seed aid. On 3 beef scale only suitable developed if be one beef seed aid or stall aid from stakeholder. Development beef cattle must be do with aggressive strategy, mean not again secunder business, but true commecial business. Direct of development must be AUDS-NAD system (Region supperior agribusiness based beef cattle in Aceh) are integrited of development of beef, organic agriculture, raising agroindustry and development of beef cattle business.Keywords: beef cattle, SWOT analyzed, poverty, agribusiness